2022
DOI: 10.1111/grow.12647
|View full text |Cite
|
Sign up to set email alerts
|

Legal land transfer rights, labor migration and urban–rural income disparity: Evidence from the implementation of China's Rural Land Contracting Law in 2003

Abstract: Legal land transfer rights are the core of farmers' land property rights. This paper examines the urban-rural income distribution effect of legal land transfer rights, revealing the reasons and mechanisms for legal land transfer rights to reduce the urban-rural income disparity. Theoretical analysis shows that granting farmers legal land transfer rights and enhancing the protection of land transfer rights can help promote rural labor migration, thereby reducing the urban-rural income disparity. This study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
1
2
0
1
Order By: Relevance
“…However, this study revealed that cultivated land still exerts a very important pull on out‐migration choices, but that the homestead seems to have no significant effect. This is consistent with the results of prior research (Hao & Tang, 2015; Xie et al., 2022; Ye, 2018). Agricultural land management practices have prompted growing concern among farmers regarding the growth of food crops.…”
Section: Discussionsupporting
confidence: 93%
“…However, this study revealed that cultivated land still exerts a very important pull on out‐migration choices, but that the homestead seems to have no significant effect. This is consistent with the results of prior research (Hao & Tang, 2015; Xie et al., 2022; Ye, 2018). Agricultural land management practices have prompted growing concern among farmers regarding the growth of food crops.…”
Section: Discussionsupporting
confidence: 93%
“…Wu et al conducted a study using data from 2011 to 2014 in rural China, which revealed that farmer participation in land transfer led to a significant reduction in fertilizer application intensity in a grain-growing region in Western China [91]. Xie et al analyzed the legal land transfer rights granted to farmers in rural China from 1999 to 2008 and found that enhancing these rights could promote urban-rural labor migration and reduce income disparities [92]. Tang et al explored the relationship between agricultural land transfer and carbon emissions using panel data from 30 provincial regions from 2005 to 2019 [93].…”
Section: Impact Of Land Transfer Behavior (Str) On Farmers' Livelihoo...mentioning
confidence: 99%
“…1. Melengkapi persyaratan proses perubahan nama pemegang hak tanggungan di Kantor Pertanahan (Xie, 2022). 2.…”
Section: Tanggung Jawab Kreditur Atas Proses Ganti Nama Pemegang Hak ...unclassified